1.3 Concerns, Version 1.0 - Fedora and the Preservation of University Records Project (Tufts Archival Research Center, 2005)
Six attributes implicit in all requirements of the Requirements for Trustworthy Recordkeeping Systems and the Preservation of Electronic Records in a University Setting, and all the steps in the Ingest Guide and the Maintain Guide.